2010
DOI: 10.1530/eje-09-0697
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin: serum levels, promoter polymorphism, and associations with birth size and cardiometabolic outcome in young adults born large for gestational age

Abstract: Objective: To assess whether the K11391GOA polymorphism in the regulatory region of the adiponectin gene (ADIPOQ) is associated with birth size, postnatal growth, adiponectinemia, and cardiometabolic risk in adult life. Design: Case-control study nested within a prospective cohort of 2063 community subjects born in 1978/1979 and followed since birth to date. Methods: ADIPOQ K11391GOA genotype-phenotype associations were evaluated in 116 subjects born large for gestational age (LGA) and 392 gender-matched contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Furthermore, among children born LGA, the risk of childhood overweight is modified by infant catch-down growth, with the highest risk of being overweight when not showing catch-down growth. This is in line with the study by Bueno et al among 116 children born LGA, showing that catchdown growth was associated with a lower BMI and abdominal circumference at the age of 23-25 years (29). Longer follow-up in this study population and other populations is needed to assess whether these associations persist and other associations develop in adolescence and adulthood.…”
Section: à2supporting
confidence: 90%
“…Furthermore, among children born LGA, the risk of childhood overweight is modified by infant catch-down growth, with the highest risk of being overweight when not showing catch-down growth. This is in line with the study by Bueno et al among 116 children born LGA, showing that catchdown growth was associated with a lower BMI and abdominal circumference at the age of 23-25 years (29). Longer follow-up in this study population and other populations is needed to assess whether these associations persist and other associations develop in adolescence and adulthood.…”
Section: à2supporting
confidence: 90%
“…A case-control study in the Brazilian population demonstrated that the rs17300539 A allele in ADIPOQ was significantly associated with an increased chance of large-for-gestational-age birth, but the study did not measure circulating adiponectin levels at birth. 40 Because the rs17300539 A allele is very rare in Japanese (monoallelic in HapMap JPT and HapMap CHB), we did not genotype rs17300539 in our study. 41 We showed that the positive correlation between the rs266729 SNP in ADIPOQ and birth weight s.d.…”
Section: Adiponectin Snps and Cord Blood Adiponectin M Saito Et Almentioning
confidence: 99%
“…Children born small (SGA) and large (LGA) for gestational age are at greater risk of developing type 2 diabetes and cardiovascular disease as they age [1][6]. These groups have been shown to have metabolic alterations in childhood and adolescence, suggesting a phenotype of metabolic dysfunction in early life, finally leading to the emergence of disease in adulthood [2], [6][10].…”
Section: Introductionmentioning
confidence: 99%